Interactive Learning Media with Realistic Mathematics Approach: Facilitating Distance Learning on Linear Program Materials - Lisa Mei Lindasari; Farida Farida (Online Learning In Educational Research (OLER), 2021)
This research produced an interactive learning media for Linear Programming material using a valid, engaging, and practical, realistic mathematics approach to facilitate distance learning. This research was development research using the ADDIE development model. The data analysis techniques used were validation analysis of media and material experts, students' responses questionnaire, and Effect Size test. The sampling used was cluster random sampling. The test subjects were fourth-semester students of classes A, C, D, E of the Mathematics Education Study Program of UIN Raden Intan Lampung. The media experts validation obtained an average score of 3.37, and the average score of material experts validation was 3.53, both within the "valid" category. The attractiveness test during the small-scale trial obtained a score of 3.52 (very attractive), and the large-scale trial obtained a score of 3.56 (very attractive). The effectiveness of the developed product obtained through the Effect Size test was 0.43 (moderate category).